Redox-manipulating nanocarriers for anticancer drug delivery: a systematic review - Xuan Meng; Yongli Shen; Huanyu Zhao; Xinlei Lu; Zheng Wang; Yanjun Zhao (Journal of Nanobiotechnology, 2024)
Abstract Spatiotemporally controlled cargo release is a key advantage of nanocarriers in anti-tumor therapy. Various external or internal stimuli-responsive nanomedicines have been reported for their ability to increase drug levels at the diseased site and enhance therapeutic efficacy through a triggered release mechanism. Redox-manipulating nanocarriers, by exploiting the redox imbalances in tumor tissues, can achieve precise drug release, enhancing therapeutic efficacy while minimizing damage to healthy cells. As a typical redox-sensitive bond, the disulfide bond is considered a promising tool for designing tumor-specific, stimulus-responsive drug delivery systems (DDS). The intracellular redox imbalance caused by tumor microenvironment (TME) regulation has emerged as an appealing therapeutic target for cancer treatment. Sustained glutathione (GSH) depletion in the TME by redox-manipulating nanocarriers can exacerbate oxidative stress through the exchange of disulfide-thiol bonds, thereby enhancing the efficacy of ROS-based cancer therapy. Intriguingly, GSH depletion is simultaneously associated with glutathione peroxidase 4 (GPX4) inhibition and dihydrolipoamide S-acetyltransferase (DLAT) oligomerization, triggering mechanisms such as ferroptosis and cuproptosis, which increase the sensitivity of tumor cells. Hence, in this review, we present a comprehensive summary of the advances in disulfide based redox-manipulating nanocarriers for anticancer drug delivery and provide an overview of some representative achievements for combinational therapy and theragnostic. The high concentration of GSH in the TME enables the engineering of redox-responsive nanocarriers for GSH-triggered on-demand drug delivery, which relies on the thiol-disulfide exchange reaction between GSH and disulfide-containing vehicles. Conversely, redox-manipulating nanocarriers can deplete GSH, thereby enhancing the efficacy of ROS-based treatment nanoplatforms. In brief, we summarize the up-to-date developments of the redox-manipulating nanocarriers for cancer therapy based on DDS and provide viewpoints for the establishment of more stringent anti-tumor nanoplatform. Graphical abstract